THE IMPACT OF SOCIAL STRUCTURE ON SMALLHOLDERS PARTICIPATIVE BEHAVIOUR IN CERTIFIED SUSTAINABLE PALM OIL SCHEME - AHMAD RIZAL, AMMAR REDZA (2020)
The demand for palm oil is steadily increasing where global consumption has reached 77 million metric tons or equivalent to 7kg of palm oil used by each person in the world annually.